PERSEPSI MAHASISWA BIMBINGAN DAN KONSELING TERHADAP PERNIKAHAN DI KALANGAN MAHASISWA - Sarah Sarah; Rosmawati Rosmawati; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Students are at the age of 18-21 represents the age of transition from teenager to adult. There’s no such an illegal thing for this age to married. But, it is not an easy thing for student, because they need to be responsible as a student also as a husband/wife at the same time. Indeed, not so many students want to married while still studying. It’s all about a choice. Student has their own perception about marriage. The purpose of this research is to find out Students Guidance and Conseling Perceptions of Marriage Among College Students. The data collection instrument with questionnaire. The sample of this research is 137 BK UR students, period 2014-2017. The sampling method is Simple Random Sampling. The result of this study indicate that most of BK students have a good perception with marriage. Although the perception of students is good enough, but still many students choose to not married, because being married while studying cause impacts and problems. Conclusion, student perception toward marriage among student, that is 1) understanding of student to marriage, is: meaning of marriage is marriage is arranged by both family; the benefits of marriage according to the understanding of the student is married can teach themselves responsible; the cause of student marriage is matchmaking; the impact is to reduce household harmony, caused by emotions that are still unstable; the problem is the students become unfettered. 2) Student assessment of marriage, is: marriage occurs because following a friend who has been married.Key Words: marriage, perception